2001
DOI: 10.1074/jbc.m011061200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Semliki Forest Virus E1 Protein inEscherichia coli

Abstract: Exposure of Semliki Forest virus 1 to mildly acidic conditions results in conformational changes of the viral spike proteins, which in turn leads to a pore formation across its membrane. The ability to form a pore has been ascribed to the ectodomain of the Semliki Forest virus (SFV) E1 spike protein. To elucidate whether the E1 protein per se is sufficient for low pH-dependent pore formation, we expressed E1 in Escherichia coli in an inducible manner using the pET11c expression system. The data obtained clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…SF virus particles from which lipid and the E2 protein were removed by protease treatment in the presence of detergent did retain a residual infectivity (Omar & Koblet, 1988). Furthermore, it has been shown that SF virus E1 protein expressed in E. coli is incorporated into the bacterial plasma membrane and that these membranes become permeable to [ 3 H]choline at low pH (Nyfeler et al, 2001). Comparable results have been obtained in similar experiments using eukaryotic cells (Dick et al, 1996).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…SF virus particles from which lipid and the E2 protein were removed by protease treatment in the presence of detergent did retain a residual infectivity (Omar & Koblet, 1988). Furthermore, it has been shown that SF virus E1 protein expressed in E. coli is incorporated into the bacterial plasma membrane and that these membranes become permeable to [ 3 H]choline at low pH (Nyfeler et al, 2001). Comparable results have been obtained in similar experiments using eukaryotic cells (Dick et al, 1996).…”
Section: Discussionsupporting
confidence: 70%
“…The molecular basis of this process has remained elusive. A series of analyses of changes in membrane permeability in cells that had accumulated alphavirus membrane proteins have been made by C. Kempf and coworkers (Kempf et al, 1987;Schlegel et al, 1991;Dick et al, 1996;Käsermann & Kempf, 1996;Nyfeler et al, 2001). These authors studied the permeability of the plasma membrane of cells late in infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro analyses of the disassembly of alphavirus cores indicated that a flow of protons through this pore from the endosome into the cytoplasm may be involved in the regulation of disassembly of alphavirus cores in vivo (Wengler & Wengler, 2002). These results and important earlier experiments (Lanzrein et al, 1993;Dick et al, 1996;Nyfeler et al, 2001) led us to conclude that the E1 protein of alphaviruses is not only responsible for fusion but probably has an additional function, namely the ability to form an ion-permeable pore in the target membrane after fusion (Wengler et al, 2003).…”
Section: Introductionsupporting
confidence: 48%
“…The fusion proteins of alphaviruses (family Togaviridae ; reviewed by Schlesinger & Schlesinger, 2001) and flaviviruses (family Flaviviridae ; reviewed by Lindenbach & Rice, 2001) are class II fusion proteins. These proteins have two additional functions: they generate an icosahedral lattice on the viral surface (Lescar et al , 2001; Pletnev et al , 2001) and they form ion-permeable pores in the target membrane during virus entry (Carrasco, 1995; Nyfeler et al , 2001; Wengler et al , 2003). Alphaviruses can be adsorbed to cells, and exposure to low pH activates virus entry at the plasma membrane (White et al , 1980; Paredes et al , 2004).…”
Section: Introductionmentioning
confidence: 99%